PEMAHAMAN KOMPETENSI ABAD 21 DALAM FILM FREEDOM WRITERS (2007) - Arbi, Anggun Purnomo; Prasetyo, Muhammad Andi Tanri; Akhlish, Muhammad (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to analyze the understanding of 21st century competencies reflected in the film "Freedom Writers (2007)". In the theoretical framework used, there are four main competencies (4C), communication, creativity, critical thinking, and collaboration, which are very relevant for the development of students in the digital era. This research used a descriptive qualitative research method with a content analysis approach to the scenes in the movie. The results identified 20 scenes in the movie reflecting an understanding of 21st century competencies. The movie illustrates how the teacher, Erin Gruwell, applies these competencies in teaching in a creative and inclusive way. The movie provides insights into the potential of film as a current educational learning tool in the face of the digital age.